Impact of Financial Threat on the Change of Investor Behavior: The Moderating Effect of Social Support During Covid-19 in Pakistan - Mehdi, Hussain; Malik, Shaukat; Ali, Huma; Rasool, Zeeshan (Universidad Pedagógica y Tecnológica de Colombia, 2021)
This paper purpose is to investigate the background of financial threat and its relationship to the indi-vidual ́s proclivity to change their financial behavior and health. Study population includes small investors in life insurance policies. Explanatory research design is used to know the causal relationship between all the variables. Primary data collected through questionnaires applied personally to the respondents were used. Respondents were randomly selected and questionnaires were appropriately applied to make easier data collection. Different Smart PLS3 data techniques were used for data inferences. This study explores that both economic problems and finan-cial anxiety are definitely associated with financial threat, and that financial threat is also significantly related to willingness to change financial behavior and psychological distress. This research reveals likewise that financial threat mediates between both independent and dependent variables. The most novel contribution of this study is the role of social support which significantly moderates the relationship between financial threat and the willingness to change financial behavior. This study is an important input in existing literature about financial threats, it provides excellent practical suggestions for household individual investors and highlights the problems experienced by these small investors.